ANALISIS KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA PADA BANK UMUM SWASTA NASIONAL DEVISA DI BURSA EFEK INDONESIA TAHUN 2015 – 2017 - Andi Wahyu Setiawan; Untung Sriwidodo; Suprihatmi Sri Wardiningsih (Universitas Slamet Riyadi, 2020)
The purpose of this research is to analyze the significance of the influence of the NPL, LDR, ROA, GCG and the CAR partially or simultaneously against profit growth on a national private commercial banks foreign exchange in Indonesia stock exchange years 2015 - 2017. The population in this research are all Public national private foreign exchange Banks that have been listed or listed on the Indonesia stock exchange in the period 2015 - 2017 of 28 banks, the number of samples that used as many as 16 banks with sampling techniques using a purposive sampling. Data analysis technique used is a classic assumption test, multiple linear regression analysis, t-test, F-test, and the coefficient of determination. The research results obtained the conclusion that Non Performing Loan negative effect significantly to profit growth. Loan to Deposit Ratio of negative effect is not significantly to profit growth. Return On Assets of positive effect significantly to profit growth. The positive effect of good Corporate Governance are not significantly to earnings growth. Capital Adequacy Ratio of positive effect is not significantly to profit growth. NPL, LDR, ROA, GCG and the CAR simultaneously effect significantly to earnings growth.